Bleomycin-induced flagellate-like skin pigmentation in a 15-year-old girl: a case report and review - Chen, Xinrong; Zheng, Chuangjie; Wang, Ke; Zhai, Linzhu (Frontiers in Medicine, 2025)
We present a detailed report of a case of flagellar-like skin pigmentation observed in a 15-year-old female patient diagnosed with ovarian yolk sac tumor following administration of a chemotherapy regimen containing bleomycin. After three cycles of chemotherapy, the patient exhibited characteristic painless, non-pruritic linear hyperpigmentation on her trunk and back. This case underscores the significance of paying attention to bleomycin-associated dermal toxicity, emphasizing the need for its early detection and management to alleviate the patient’s psychological and physical distress. Our research indicates that additional studies are necessary to comprehensively understand the underlying mechanisms of flagellar-like skin pigmentation and to identify effective prevention and treatment approaches.